Making theater without making theater: Telatralities and performavirtualities as a route in pandemic times (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aims to share artistic and pedagogical experiences lived in the context of the technical course in theater at the Centro Interescolar de Cultura, Arte, Linguagens e Tecnologias (Cicalt) carried out during the Special Regime of Non-Presential Activities established by the Secretary of Education of Minas Gerais as a protective measure during the Covid-19 pandemic. The experiences reported were based on the notion of performativity explored in virtual scenic experiments, generating telatralities and performavirtualities. It was reflected about the continuity of teaching and theatrical practice in the pandemic context from the construction of anti-structures that point to alternative routes for pedagogical artistic practices.
Keywords: Theater teaching; Covid-19 pandemic; Special Regime for Non-Presential Activities; Performativity